(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Flexing culture, which refers to the act of showcasing wealth and social status, has become a common phenomenon in the digital era, especially on social media. This culture represents a materialistic lifestyle that has the potential to create social inequality and spiritual crises. This study aims to analyze flexing culture from the perspective of the Qur’an by highlighting its contradiction with the values of tauhid. The research employs a descriptive qualitative method using a thematic interpretation (tafsir maudhu’i) approach, analyzing Qur’anic verses related to wealth, arrogance, and worldly life. This study finds that flexing culture contradicts the principle of tauhid, as it promotes behaviors such as arrogance (takabbur), ostentation (riya’), and wastefulness (israf), all of which are criticized in the Qur’an. In contrast, the Qur’an emphasizes the importance of simplicity, gratitude, and the responsible use of wealth. In conclusion, flexing culture is inconsistent with Qur’anic values and should be addressed through the strengthening of spiritual awareness and ethical use of social media.